“Muhammed b. Gazi’nin, Ravzatu’l-Ukul adlı Eseri Üzerine Bir İnceleme / A Review on Ravzat al-Uqul by Muhammad b. Ghazi - Gültekin, Aladdin (Journal of History Culture and Art Research, 2018)
Abstract Poetry and story have long been an important and effective methods to express the feelings and thoughts in terms of language and literature. Muhammed b. Gazi el-Malatyavi applied this method in his book called Ravzat al-Uqul, which contains ninety-six stories in Arabic and Persian. In every story, the number of couplets and parables differs. Not limited to a certain period, the couplets are belong to poets in every periods of Arabic and Persian literature. The poems which are given as examples are chosen according to the main theme, to the extent that they can be used as a title of the story. They include advice to have a positive impact on the characters. Also they does not contain any complicated word and phrase. Öz Dil ve edebiyat açısından şiir ve hikayeler, öteden beri insanların maksadını anlatmak istedikleri önemli ve etkili bir yöntem olmuştur. Muhammed b. Ġāzî el-Malatyavî de bu yöntemi Ravżatu’l-ʿuḳūl adlı eserinde uygulamıştır. Arapça ve Farsça çok sayıda şiir ve meselin bulunduğu bu eserde doksan altı hikâye yer almaktadır. Her hikâyede beyit ve mesel sayısı aynı olmayıp değişim göstermektedir. Beyitler Arap ve Fars edebiyat tarihinin bütün dönemlerine ait şairlere ait olup, belli bir dönemle sınırlandırma olmamıştır. Örnek verilen şiirler, hikâyenin başlığı olabilecek derecede ana temaya uygun seçilmiş, kişilerin karakterlerini olumlu yönde etkileyecek kadar tecrübe ve öğüt içermektedir. Ayrıca anlaşılması zor kelime ve terkip içermemektedir.